The Relations of Knowledge, Attitude, and Motivation, General Surgeons and Nurses, Toward Nosocomial Infection Prevention Practices Inside the Operating Room - Muhammad Nazhim; Enrico Adhitya Rinaldi; Fresley Hutapea (CV. Inara, 2026)
This study aims to analyze the effect of knowledge, attitudes, and motivation on healthcare workers’ service performance in the context of infection prevention in operating rooms. The study employed a quantitative approach with a cross-sectional design. The population consisted of all healthcare workers involved in operational services at RSUD H. Hanafie Muara Bungo, Indonesia, using a total sampling technique with a sample size of 30 respondents. Data was collected through structured questionnaires and analyzed using Spearman correlation and linear regression. The findings indicate that knowledge does not have a significant effect on service performance, while attitudes show a significant relationship with moderate strength. Motivation emerges as the most dominant factor, exhibiting a strong and significant relationship with service performance. Simultaneously, knowledge, attitudes, and motivation significantly influence service performance, contributing 53.4% to its variance. These findings suggest that service performance is not solely determined by cognitive aspects but is strongly influenced by behavioral and motivational factors. Therefore, improving service quality requires an integrated managerial approach focusing on strengthening motivation and fostering professional attitudes, alongside enhancing workforce competencies.